Isolation and characterization of circulating tumor cells in prostate cancer - Diamond, Elan S.; Lee, Guang Yu; Akhtar, Naveed H.; Kirby, Brian; Giannakakou, Paraskevi; Tagawa, Scott T.; Nanus, David (Frontiers in Oncology, 2012)
Circulating tumor cells (CTCs) are tumor cells found in the peripheral blood that originate from established sites of malignancy and likely have metastatic potential. Analysis of circulating tumor cells CTCs has shown great promise as a prognostic marker as well as a potential source of novel therapeutics. Isolation and characterization these cells for study, however, remain challenging due to their rarity in comparison with other cellular components of peripheral blood. Several techniques that exploit the unique biochemical properties of CTCs have been developed to facilitate isolation of these cells. Positive selection of CTCs is achieved using microfluidic surfaces coated with antibodies against epithelial cell markers or tumor specific antigens such as EpCAM or prostate specific membrane antigen (PSMA). Following isolation, characterization of CTCs may help guide clinical decision-making. For instance, molecular and genetic characterization may shed light on the development of chemotherapy resistance and mechanisms of metastasis without the need for tissue biopsy. This paper will review novel isolation techniques to capture CTCs from patients with advanced cancers, as well as efforts to characterize the CTCs. We will also review ways in which these analyses can assist in clinical decision-making, Conclusion: The study of CTCs provides insight into the molecular biology of their tumors of origin that will eventually guide the development tailored therapeutics. These advances are predicated on high yield and accurate isolation techniques that exploit the unique biochemical features of these cells.